Altered frontal aslant tracts as a heritable neural basis of social communication deficits in autism spectrum disorder: A sibling study using tract‐based automatic analysis. Issue 2 (12th December 2018) - Lo, Yu‐Chun; Chen, Yu‐Jen; Hsu, Yung‐Chin; Chien, Yi‐Ling; Gau, Susan Shur‐Fen; Tseng, Wen‐Yih Isaac
Abstract : Investigating social behaviors and brain structural alterations in unaffected siblings of individuals with autism spectrum disorder (ASD) may help identify intermediate phenotypes of social communication deficits in ASD. This study hypothesized that such intermediate phenotypes could be identified in white matter tracts of the social communication model that exhibited reduced tract integrity and associations with social communication deficits. Boys with ASD ( N = 30), unaffected male siblings ( N = 27), and typically developing (TD) boys ( N = 30) underwent clinical evaluation and MRI scanning. Group differences in generalized fractional anisotropy (GFA) values, a white matter integrity index derived from diffusion MRI data, and the relationships of GFA with the Social Responsiveness Scale (SRS) scores and the Child Behavior Checklist (CBCL/4–18) scores were investigated. Significant differences were found in the GFA values of the frontal aslant tract (FAT) among the three groups, with the decreasing order of GFA from TD to siblings to ASD. The GFA values of the FAT were associated with the social communication scores (on the SRS) in the sibling group, and those of the superior longitudinal fasciculus III were associated with the social problems scores (on the CBCL/4–18) in the boys with ASD. Due to the altered tract integrity and association with social communication deficits in the unaffected siblings of individuals with ASD, the FAT might be a heritable neural basis for social communication deficits of ASD. Autism Res 2019, 12: 225–238 © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Autism spectrum disorder (ASD) is a group of highly heritable disorders with social communication deficits as one of the core symptoms. This study aimed to identify a neural trait of social communication deficits in individuals with ASD. We investigated brain structural alterations and their associations with social communication scores in unaffected siblings of individuals with ASD. The siblings' frontal aslant tract was found to be impaired, and this tract showed a significant association with the social communication scores. Our findings support that the frontal aslant tract might be a potential neural trait of social communication deficits in ASD.